A Case Report: First Long-Term Treatment With Burosumab in a Patient With Cutaneous-Skeletal Hypophosphatemia Syndrome - Merz, Lea Maria; Buerger, Florian; Ziegelasch, Niels; Zenker, Martin; Wieland, Ilse; Lipek, Tobias; Wallborn, Tillmann; Terliesner, Nicolas; Prenzel, Freerk; Siekmeyer, Manuela; Dittrich, Katalin (Frontiers in Endocrinology, 2022)
Epidermal nevus syndromes encompass a highly heterogeneous group of systemic disorders, characterized by epidermal nevi, and a spectrum of neuromuscular, ocular, and bone abnormalities. Cutaneous-skeletal hypophosphatemia syndrome (CSHS) constitutes a specific sub-entity in which elevated levels of fibroblast growth factor-23 cause hypophosphatemic rickets that are, to date, not amenable to causal therapy. Here, we report the first long-term follow-up of causal treatment with burosumab in a 3-year-old female patient with CSHS. 4 weeks after initiation of burosumab treatment, serum phosphate normalized to age-appropriate levels. Furthermore, long-term follow-up of 42 months revealed significant improvement of linear growth and gross physical functions, including respiratory insufficiency. Radiographic rickets severity as well as subjective bone pain were strongly reduced, and no side effects were observed over the course of treatment. In summary, we, here, report about a successful treatment of hypophosphatemic rickets in CSHS with burosumab over the time course of 42 months. In our patient, burosumab showed convincing efficacy and safety profile, without any loss of effect or increase of dose.